Eprinomectin pour-on for control of Boophilus microplus (Canestrini) ticks (Acari: Ixodidae) on cattle - Aguirre, Héctor David (2005)
The efficacy of a commercial pour-on formulation of eprinomectin, a macrocyclic lactone, against experimental infestations of Boophilus microplus (Canestrini) ticks was evaluated in two trials involving 27 Bos taurus calves. The first trial was designed to evaluate the effects of a single treatment at a dose of 0.5 mg/kg of body weight against standard size B. microplus females (4.5–8.0 mm long). A significant reduction in tick numbers (P < 0.05, Wilcoxon test) was observed between treated calves as compared to untreated ones from Day 3 (44% efficacy) after treatment to the end of the trial on Day 28 (96.9%), with a peak efficacy of 97.1% on Day 21. In the second trial the effect of eprinomectin on standard size tick numbers, engorgement weight and fertility of female ticks from calves with a single treatment dose of 1 mg/kg on Day 0 and calves treated twice at a dose of 0.5 mg/kg on Days 0 and 4 was evaluated. An efficacy >93% was obtained from Day 2 to Day 28 after treatment in calves treated twice at 0.5 mg/kg, and to the end of the trial (Day 35) in calves treated once with 1 mg/kg. The 1 mg/kg treatment provided >98% residual efficacy for at least 7 days. During the first part of the second trial the efficacy of eprinomectin resulted from a dramatic adverse effect on engorgement weight and fertility of female ticks, with 100% control on Day 5 (dosage of 1 mg/kg) and on Days 6 and 7 (two doses of 0.5 mg/kg). Following Day 7, most of the effect was due to reduction in the number of standard size female ticks.